Case Presentation : Congenital Tuberculosis in A Premature Infant Presented with Miliary Tuberculosis - Indra Ihsan; Aldian Tri Wahyuda Putra; Mutia Rahman (Scientific Journal, 2025)
Congenital tuberculosis (TB) is a rare neonatal infection resulting from vertical transmission of Mycobacterium tuberculosis from mother to infant. Fewer than 500 cases have been reported worldwide, with a high mortality rate up to 40%. Diagnosis is challenging due to its nonspecific presentation and resemblance to neonatal sepsis. We report a case of a 1-month-old preterm infant admitted with worsening respiratory distress, fever, and cough. Chest X-ray revealed a “snow storm appearance” consistent with miliary tuberculosis. The infant’s mother had a history of chronic cough prior to pregnancy and later tested positive for Mycobacterium tuberculosis by sputum PCR. The sputum PCR test in the infant also returned positive. Laboratory findings included leukocytosis with neutrophil predominance and elevated transaminases.  The infant was given respiratory support with CPAP and treated with a standard four-drug antitubercular regimen (2HRZE/10HR) and corticosteroids due to severe respiratory involvement. The clinical course was favorable, with resolution of respiratory symptoms and radiologic improvement, allowing discharge after 16 days of hospitalization. The diagnosis of congenital tuberculosis in this patient was confirmed based on the mother's history of suspected pulmonary tuberculosis prior to pregnancy, along with the confirmed diagnosis of tuberculosis through a positive sputum PCR test in the mother and the infant. Liver biopsy which is gold standard of diagnosis could not be performed due to the patient's unstable condition and the consideration of the benefit invasive procedure.Awareness of maternal risk factor for TB plays a pivotal role in suspected congenital tuberculosis, enables early diagnosis and prompt treatment, reducing mortality and long-term sequelae.